From Challenging Culture to Challenged Culture - Leman, Johan (Studia Anthropologica, 1987)
The First Part of the book, A Challenging Culture, presents the socio-cultural code in Sicily as observed in the Province of Caltanissetta. The most important structural and geographical factors that are culturally relevant are discussed. The Sicilian culture emerges gradually as a culture of control and challenge, and it is on the basis of this idea that Part II, From Challenge to Change, is developed.